Blood coagulopathy and dysregulated circulating proteins associated with type 2 diabetes mellitus - Maphumulo, Siphosethu Cassandra (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.